2010
DOI: 10.1371/journal.pone.0009305
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Gain of Function Contribution of AKT to Mammary Tumorigenesis in Mouse Models

Abstract: Elevated expression of AKT has been noted in a significant percentage of primary human breast cancers, mainly as a consequence of the PTEN/PI3K pathway deregulation. To investigate the mechanistic basis of the AKT gain of function-dependent mechanisms of breast tumorigenesis, we explored the phenotype induced by activated AKT transgenes in a quantitative manner. We generated several transgenic mice lines expressing different levels of constitutively active AKT in the mammary gland. We thoroughly analyzed the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 68 publications
1
26
0
Order By: Relevance
“…Our studies in mouse models with activated AKT or PI3Ka indicated that the activation of these oncogenes do not fully recapitulates the tumorigenic phenotype of PTEN loss [85][86][87]. We have observed an increase in benign lesions, as expected, if senescence is induced upon PI3K and AKT activation [44,88], perhaps by AKT or PI3K activation in a progenitor cell unable to progress to full tumorigenesis. On the other hand, Majumder and colleagues [89] recently published their fi nding that a p27kip1-dependent checkpoint also induces senescence upon AKT activation and that ablation of this checkpoint allows progression from PIN to carcinoma.…”
Section: The Pi3k/foxo Pathway In Senescencementioning
confidence: 57%
See 2 more Smart Citations
“…Our studies in mouse models with activated AKT or PI3Ka indicated that the activation of these oncogenes do not fully recapitulates the tumorigenic phenotype of PTEN loss [85][86][87]. We have observed an increase in benign lesions, as expected, if senescence is induced upon PI3K and AKT activation [44,88], perhaps by AKT or PI3K activation in a progenitor cell unable to progress to full tumorigenesis. On the other hand, Majumder and colleagues [89] recently published their fi nding that a p27kip1-dependent checkpoint also induces senescence upon AKT activation and that ablation of this checkpoint allows progression from PIN to carcinoma.…”
Section: The Pi3k/foxo Pathway In Senescencementioning
confidence: 57%
“…It is possible that the induction of the senescent checkpoint is not a direct effect of PI3K pathway deregulation but a general checkpoint imposed on the progression from benign to malignant tumours. However, in mouse models, activation of AKT1 in the mammary gland triggers senescence that seems to be dependent upon p16 activation but not of p27 or p53 absences [44,86].…”
Section: The Pi3k/foxo Pathway In Senescencementioning
confidence: 97%
See 1 more Smart Citation
“…Studies in murine mouse models have shown that p53 is the preferred mutation upon PTEN loss. In constitutively active AKT or PI3K transgenic models, an increase in benign lesions are observed if senescence is induced upon AKT activation (Blanco-Aparicio et al 2010 ;Renner et al 2008 ).…”
Section: Effector Pathwaysmentioning
confidence: 99%
“…29 Other studies have shown that aberrant AKT activation has a critical role in tumorigenesis. 30 In this study, we identified small RNAs in lung cancer cells. To analyze a novel miRNA signature, we examined the structure and sequence of the small RNAs, analyzed the expression patterns of the novel miRNAs in lung cancer tissues and assessed the miRNA target genes.…”
mentioning
confidence: 99%